ASSESSMENT ON WEB SLOPE OF TRAPEZOIDAL RIB IN ORTHOTROPIC DECKS USING FEM - Fettahoglu, Abdullah (YILDIZ TECHNICAL UNIV, 2014)
Thanks to their light weights, orthotropic deck structure is commonly used in industry to span long distances. An orthotropic deck is composed of deck plate, ribs and cross-beams. The deck is referred to as orthotropic, because it is generally assumed as a simple plate having two different stiffnesses in longitudinal and transverse directions. Ribs provide the longitudinal stiffness of the bridge, whereas cross-beams provide transverse stiffness. Cross-beams are broadly of the similar shapes; nevertheless ribs can possess several different shapes like strip, bulb, angle, V-shaped, U-shaped, sektkelch or trapezoidal. This study is focused on trapezoidal ribs, since they are dominantly used in industry. Three different slopes of trapezoidal rib web are assessed using FEM, while rib width, height, span and thickness are kept constant. Results show that stresses especially of cross-beam and deflections of deck plate change depending on slope of trapezoidal stiffener webs.
Keywords: Orthotropic deck; stress analysis; longitudinal stiffener; trapezoidal rib; FEM; Engineering